On the diffusion current in a MOSFET operated down to deep cryogenic temperatures. (February 2021) - Ghibaudo, G.; Aouad, M.; Casse, M.; Poiroux, T.; Theodorou, C.
Highlights: A detailed analysis of diffusivity in a 2D inversion layer is carried out. Comprehensive study of diffusion and drift current components in a MOSFET. New formulation of diffusion noise valid from weak to strong inversion. Abstract: A detailed and didactic analysis of the diffusivity in a 2D inversion layer is carried out, providing its dependence on carrier density and temperature. Then, a comprehensive study of the diffusion and drift current components in a MOSFET is proposed. Their dependence with gate and drain voltages is investigated down to deep cryogenic temperature, revealing that at T = 4 K the diffusion current is nearly constant in strong inversion whatever the mobility law. Finally, based on our diffusivity analysis, a new formulation of the diffusion noise valid from weak to strong inversion down to very low temperature has been developed.